ANALISIS PENGEMBANGAN MEDIA PEMBELAJARAN KEBUGARAN JASMANI BERBASIS MULTIMEDIA INTERAKTIF - Franciska Paulina (Universitas Syiah Kuala, 2022)
The purpose of the study. This study aims to analyze the multimedia used by previous researchers to determine the level of relevance and to develop physical fitness learning (preliminary study).Materials and methods. The method used is a literature review method which describes previous research which is then analyzed and concluded in accordance with the research objectives. Library research is research that is carried out only based on written works, including research results, both published and unpublished (Embun, 2012). The problem in this research is to find out the relevance of interactive multimedia-based physical fitness learning media from the research results.Results. The results of a literature review from previous studies show that interactive multimedia (auto play media) has been applied to physical fitness learning and there needs to be the development of website-based physical fitness learning (google sites) that have not been developed previously so that it can increase the enthusiasm of students in participating in physical fitness learning.Conclusions. An interactive multimedia based fitness learning developed and effective to use. and there needs to be the development of website-based physical fitness learning (google sites) that have not been developed previously so that it can increase the enthusiasm of students in participating in physical fitness learning.